An analysis of the potential liability of classification societies: developing role; current disorder and future prospects - Durr, Sean Diederich (Department of Commercial Law, 2021)
'Put simply, the, purpose of the classification certificate is not to guarantee safety, but merely to permit Sundance to take advantage of the insurance rates available to a classed vessel'. This alarming statement made concerning the purpose of classification certificates by Judge Pratt in The Sundancer raised serious concerns regarding the reliability of classification society certificates. At a time when maritime casualties were escalating; partly due to an ageing maritime fleet, the above remark disconcerted classification societies who were attempting to restore confidence in their reputation which had been seriously impaired by, inter alia, the malpractices of some of the smaller, less scrupulous classification societies.